Cytotoxicity and ion release of alloy nanoparticles - Hahn, Anne (Springer Netherlands, 2012)
It is well-known that nanoparticles could cause toxic effects in cells. Alloy nanoparticles with yet unknown health risk may be released from cardiovascular implants made of Nickel–Titanium or Cobalt–Chromium due to abrasion or production failure. We show the bio-response of human primary endothelial and smooth muscle cells exposed to different concentrations of metal and alloy nanoparticles. Nanoparticles having primary particle sizes in the range of 5–250 nm were generated using laser ablation in three different solutions avoiding artificial chemical additives, and giving access to formulations containing nanoparticles only stabilized by biological ligands. Endothelial cells are found to be more sensitive to nanoparticle exposure than smooth muscle cells. Cobalt and Nickel nanoparticles caused the highest cytotoxicity. In contrast, Titanium, Nickel–Iron, and Nickel–Titanium nanoparticles had almost no influence on cells below a nanoparticle concentration of 10 μM. Nanoparticles in cysteine dissolved almost completely, whereas less ions are released when nanoparticles were stabilized in water or citrate solution. Nanoparticles stabilized by cysteine caused less inhibitory effects on cells suggesting cysteine to form metal complexes with bioactive ions in media.